For problems (19) through (23), solve the following quadratic in form equations. 19. \( x^{4}+10 x^{2}+9=0 \) 20. \( x^{\frac{2}{3}}-5 x^{\frac{1}{3}}+6=0 \) 21. \( 2 x^{\frac{1}{2}}-x^{\frac{1}{4}}=0 \) 22. \( (x+1)^{2}-8(x+1)-9=0 \) 23. \( 4(t-1)^{2}-9(t-1)=-2 \) 24. \( x^{-2}-x^{-1}-12=0 \)
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Extra Insights
To solve the equations, we'll use substitutions to transform them into quadratic forms, making them easier to handle. For problem 19, let \( y = x^2 \). The equation transforms to \( y^2 + 10y + 9 = 0 \). Using the quadratic formula, \( y = \frac{-10 \pm \sqrt{10^2 - 4 \cdot 1 \cdot 9}}{2 \cdot 1} \), we find the roots. This gives us potential values of \( y \), which we'll convert back to \( x \) by taking square roots. For problem 20, we substitute \( z = x^{\frac{1}{3}} \), obtaining \( z^2 - 5z + 6 = 0 \). Again applying the quadratic formula allows us to find \( z \), which we will cube to get values for \( x \). For problems 21 through 24, we follow similar approaches: recognizing patterns for substitution, utilizing the quadratic formula or factoring to solve for the transformed variables, and then converting back to the original variable. Clean and systematic transformations are key!